2015
DOI: 10.1111/echo.13026
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of D‐Dimer Levels and Tissue Doppler Mitral Annular Systolic Velocity for Detection of Left Atrial Appendage Thrombus in Patients with Mitral Stenosis in Sinus Rhythm

Abstract: Measurement of Sa and D-dimer levels is necessary for better assessment of LA thrombus and SEC, for identification of patients who are at high risk for LA thrombus formation and for initiation of prophylactic anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Characteristics of included studies are presented in Table 1 . All of the studies were observational studies, among which 8 studies [ 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 ] were prospective design. Mean age of study participants ranged from 29.7 to 76.0 years, and the percentage of males ranged from 28.4% to 77.8%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of included studies are presented in Table 1 . All of the studies were observational studies, among which 8 studies [ 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 ] were prospective design. Mean age of study participants ranged from 29.7 to 76.0 years, and the percentage of males ranged from 28.4% to 77.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve (57.1%) studies confined the population to patients with AF [ 13 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], with reported percentages of patients with AF ranged from 20%-86% in 7 (33.3%) studies [ 12 , 18 , 22 , 32 , 33 , 34 , 35 ], besides, 2 (9.5%) studies focused on patients in sinus rhythm [ 23 , 36 ], 4 studies (19.0%) restricted to the population of patients with mitral stenosis [ 23 , 33 , 35 , 36 ], among which, 2 studies reported the prevalence of mitral stenosis ranged from 6.0% to 27.5% [ 28 , 37 ]. Of 21 included studies, 12 (57.1%) studies reported mean or median DD values [ 13 , 18 , 19 , 24 , 25 , 26 , 27 , 29 , 30 , 32 , 35 , 37 ], 5 (23.8%) studies reported frequency and DD cutoff value on LAT [ 22 , 23 , 31 , 33 , 34 ], and 4 (19.0%) studies reported both [ 12 , 20 , 21 , 36 ]. 11 studies have available information to calculate a ratio of the presence of LAT among individuals in the top vs bottom third of DD levels[ ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations